Sharp Toroidal Resonances in Planar Terahertz Metasurfaces - Gupta, Manoj (2017)
A toroidal dipole in metasurfaces provides an alternate approach for the excitation of high-Q resonances. In contrast to conventional multipoles, the toroidal dipole interaction strength depends on the time derivative of the surrounding electric field.